ODSAC: An Innovative Approach for Detection of Suspicious Human Activity and Crime Prediction - Bhugul-Rajurkar, A. M.; Gulhane, V. S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The escalating crime rate has spurred a surge of research into real-time object detection for video surveillance. An automatic video detection system is required since it is challenging to continuously watch camera footage taken in public areas in order to identify any unusual activity. Real-time systems find it challenging to identify suspicious or small moving objects against a blurry background. In order to identify suspicious human activity in real-time video, this research introduces a novel algorithm dubbed ODSAC (Object Detection And Suspicious Activity Classification). Darknet53 is used by the system as an object-detecting tool. We have designed a custom classifier that accurately distinguishes whether activity is suspicious or not. The classifier is trained on a self-created dataset to ensure robust performance across various environmental conditions and scenarios. Extensive experimentation on the self-created dataset validates the effectiveness of the proposed approach. The evaluation metrics, including precision, recall, and F1 score, showcase the system's high accuracy in detecting individuals with weapons. The achieved detection accuracy of 99.31% underscores the reliability and efficiency of the architecture with the custom classifier. We have also done a comparative analysis with some existing Methods studied during the literature study. This research paper will be useful for applications such as Criminal Justice to identify suspicious criminal behaviors, Healthcare, Law Enforcement, etc. Integrating this technology with the current monitoring infrastructure might have a significant impact, especially in important locations like airports, schools, and public areas.